Et-turuku'l muasıra li isbati'l-cinayeti ve ahkamiha fi fıkhi'l -İslami - ALI, ASUDA MAHDI (Fırat Üniveristesi, 2021)
Bu tez, suçların tespitinde modern hukukta kullanılan delil ve karinelerin, İslam Hukuku açısından kullanılıp kullanılamayacağını ineceleme konusu yapmıştır. Öldürme ve yaralama, hırsızlık, zina, tecavüz ve benzeri suçları irtikâp edenlerin cezai müeyyidlerinin nısfet kaidelerine göre verilebilmesi için cezai sorumluluk sahiplerinin irtikâp ettikleri cürümlerin doğru bir şekilde tespiti son derece önemlidir. Klasik dönemler itibariyle İslam Hukukunda, bir suç ile itham edilen kişinin gerekli cezaya çarptırılması için, atılı suçun hukukun öngördüğü bir takım delillerle ispat edilmesi gerekir. Bu delillerin belli başlıları, şehadet ehliyetine sahip şahitlerin şahitlik yapması, itham eilden kişinin suçu itirafı, davacı veya davalının yeminidir. Modern zamanlarda ise kamera kaydı, görüntüleme, ses kaydı, parmak izleri, DNA testi, kan grubunu tespit testi ve benzeri yöntemler etkin bir şekilde kullanılmaktadır. Çalışmamızda bu yöntemlerin mahiyetleri hakkında bilgi verilmiş ve İslam Hukuku açısından değerlendirilmiştir. Anahtar Kelimeler: İslam Hukuku, Suçların İspatı, Modern Yöntemler, Klasik Yöntemler

This thesis examines recent evidence and evidence in criminal proof from the perspective of Islamic jurisprudence, and that proving criminal responsibility in crimes of all kinds, such as murder, theft, adultery or the like, is a major pillar of the ruling pillars of grievances and cases in Islamic law, and then conviction The accused, restoring rights to their owners, and compensating them financially, as the legal rulings are based on absolute justice. It is well known that Islamic law governs the principle of relying on evidence and evidence in criminal evidence So that the accused does not have a pretext to deny the accusation against him, and at the same time not allow the accusation to be imposed on innocent people. And since the patterns of life have changed in their various aspects, the evidence and evidence that the courts rely on to decide on judicial rulings have changed and did not remain as before them. Whereas the accused's confession, or the testimony of witnesses, were the two methods of criminal evidence, the courts today are based on recent evidence that did not exist In the era of ancient jurists, and these recent evidence include the genetic print, fingerprint, saliva, and the like As well as video clips, photographs, e-mail and more. Because of the lack of this modern evidence at the time of the jurists, it has become a topic worthy of study from a legal standpoint. The main reason for writing this letter is to demonstrate the relevance of Islamic law for every age and place, and its suitability is represented in its containment of Sharia rules that can be applied to every new issue, even if it did not exist before. On the other hand, a statement of what is related to these modern methods in terms of their relevance in being disciplined or uncontrolled from a juristic point of view. Key Words: Islamic Law, Proof of Crimes, Modern Methods
Contemporary ways to prove crime and its provisions in Islamic jurisprudence
Keywords: Din; Hukuk